Validity of echocardiographic estimates of left ventricular size and performance in infants and children. Issue 4 (April 1975) - Kaye, H H; Tynan, M; Hunter, S
Abstract : Echocardiography has been shown to be a reliable method for estimating left ventricular size and function in adults, but little attention has been paid to its application to infants and children. This paper describes a validatory study in 40 children aged between 4 days and 16 years. There was a significant correlation between angiocardiographic and echocardiographic estimates of left ventricular end-diastolic volume (r=0.76), left ventricular end-systolic volume (r=0.68), and ejection fraction (r=0.73). Left ventricular mean circumferential shortening rate (mean Vcf), however, gave the mostsignificant correlation (r=0.91). These findings indicate that while care must be exercised in interpreting indices of left ventricular size and performance derived from echocardiography, these measurements, and in particular mean Vcf, do offer a useful and reliable means of assessing left ventricular function in infants and children.